The Implementation of Genre Based Approach in Teaching Writing Recount Texts - Soraya, Kety (JEDLISH : Journal Of Education and English Language Teaching, 2022)
This study attempts to identify the effectiveness of Genre Based Approach (GBA) in teaching writing recount text. It aims to answer the following research question: what is the effect of implementing GBA on students' writing ability? This study employed a true experimental design. The data were collected from a pretest, posttest and analyses of students' texts. The researcher applied GBA to the experiment class, on the other hand, the control class was taught using a regular method, a method which generally consists lecturing, discussing and games without structured cycle process. The obtained data from pretest and posttest were calculated using a t-test to identify whether there is a significant difference between the test scores of both groups, experimental and control group. The analyses of students' texts presented were used to find the students' progress or improvement that the students make after implementing GBA The result of this study shows that GBA has a significant effect on students' writing ability. With a level of significance of 0.05, the value of t-test is higher than t-table. The result describes that there is a significant difference between the pretest and posttest scores obtained by the experimental group. In other words, there is an effect of implementing GBA on students' writing ability. With regard to the development of students' writing abilities as shown in the texts produced by the students, the student’s writing skill were significantly improved in terms of the schematic structure and linguistic features. Based on these findings, the researcher believes that GBA has the potential to improve students' writing ability, therefore she recommended that GBA be applied in the teaching writing in Indonesia.